SOSIALISASI DAN EDUKASI JAMINAN PRODUK HALAL DI RUMAH SAKIT PKU MUHAMMADIYAH GAMPING DAN ASRI MEDICAL CENTER YOGYAKARTA - Salmah Orbayinah; Ardi Pramono (Prosiding Seminar Nasional Program Pengabdian Masyarakat, 2018)
Halal and thoyib have been accepted as quality standards applied to the supply and production process of a product. Halal standards include food, cosmetic, pharmaceutical and medical products. For Muslim consumers, buying halal-certified products can guarantee hygiene and health, of course, according to Muslim shari'a. Public awareness of both consumers and businessmen on the issue of halal standards in Indonesia, especially in the area of PKU Muhammadiyah Gamping Hospital and Asri Medical Center (AMC) is still relatively low. Halal standardization should be reviewed from upstream to downstream, so more intensive socialization and education is needed to increase the knowledge and awareness of the community to be driven to halal certification. This community service program will socialize UU no.33 of 2014 on Halal Product Guarantee and the technical provisions of its application. This program will be followed by a visit to the direct field of food and beverage preparation at the hospital. Participants also receive assistance to process halal certification of their food and beverage products. Awareness of halal standards built among consumers and culinary entrepreneurs in PKU Muhammadiyah Gamping and Asri Medical Center (AMC), is expected to become the forerunner of halal kitchen and cafeteria in Yogyakarta as a tourist city, become a pilot for other culinary products entrepreneurs to the city of halal tourism.